Traditional knowledge of household products - Ghosh, Ashis Kumar, 1960- (Delhi : Daya Pub. House, 2011)
Study conducted in West Bengal, India.
Includes bibliographical references and index.
Keywords: Traditional ecological knowledge -- India -- West Bengal; Household supplies -- India -- West Bengal; Natural products -- India -- West Bengal; Sustainable development -- Environmental aspects -- India -- West Bengal; Household supplies; Natural products; Sustainable development; Traditional ecological knowledge; India -- West Bengal